(untitled) (Bulletin KNOB, 2022)
Between 1774 and 1781, Eise Eisinga built an orrery in his house in Franeker. This instrument was and is commonly referred to as a planetarium, although it also gives information about the sun, the moon and the main constellations. I use the term ‘instrument’ for the machinery above the ‘planetarium room’ and the boxbed together with the dials on the ceiling and the wall containing the box-bed (bedsteewand). I use the term ‘Planetarium’ for the institution, that is the building with everything in it. The machinery, the ceiling, and the bedsteewand have been nominated for UNESCO world heritage status this year. The aim of this article is to discuss the authenticity of the Planetarium: which parts are authentic – that is, from the time of Eisinga – which have been altered, and how were any alterations supervised? The article concentrates on the period around 1900, when the conservation of monuments had just been institutionalized, but the general principle of preferring ‘preservation over alteration’ had not yet been widely accepted. The primary sources are the annual reports on the state of maintenance by government architect Jacobus van Lokhorst. Eisinga had sold the Planetarium to the national government in 1826. In order to save money, the government gave it to the municipality of Franeker in 1859. When it was suspected that the municipality was not meeting the first condition of the agreement – to maintain the instrument at all times – Van Lokhorst was tasked with the supervision of the Planetarium by the Minister of the Interior in 1882. We know that the instrument was repaired a couple of times, but the exact nature of the alterations is unknown, because Van Lokhorst barely mentions them in his reports. He had to leave the supervision of the instrument to the caretaker and a clockmaker, because he was out of his depth. The only parts of the ‘planetarium room’ that remained authentic around 1900 are the ceiling and the bedsteewand. After the instrument had come to a standstill several times, a stove had to be installed to decrease the humidity in the room. That is why in 1890 the windows were replaced to make room for a chimney. The rest of the room was turned into a period room on the advice of Van Lokhorst and with permission of the Minister of the Interior: the walls were whitewashed and, a year later, the floor was tiled. The tile wainscoting dates from 1895. The conclusion is that the authenticity of the Planetarium decreased around 1900. This should not affect the UNESCO nomination. Repairs to the machinery were only to be expected, and the ceiling and the bedsteewand appear to be authentic. However, a world heritage site attracts more visitors, all of whom have to be facilitated. How will this affect the authenticity of the Planetarium in the future?